Benefits of block programming using Sphero mini as a mobile application in higher education - Prado Ortega, Mauricio Xavier (2023)
The use of commands and coding through a programming language is undoubtedly complex for students who are inclined to study software and applications. However, the block programming environment using instruments focused on educational robotics with a robot like Sphero mini that combines the use of mobile phones as a learning strategy, is changing this perspective in higher education. Under these conditions, the objective is to identify the benefits of block programming on training in the educational robotics subject in university students. A documentary review of articles related to the subject was carried out, the methodology used is part of a non-experimental mixed approach, for which it was applied as a data collection technique through an online survey that collects the points of view and benefits of mobile learning when working with a robotic sphere of a population number of 30 students of the Pedagogy of Experimental Sciences career of the Technical University of Machala for the academic period 2022-2. Among the results, the study shows that block programming conforms to the new STEAM standards and active methodologies for the learning of students who want to professionally use the teaching of educational robotics as part of the technology and interaction of intelligent devices that have been coupled to the contemporary and modern age. The benefits that the students evidenced from block programming through mobile learning are the ease of use of the application, portability on your mobile device, easy to learn, drag and drop features, connectivity and storage, tracking in real time by executing an educational robot and facility for error detection.